Dating the Neolithic human remains at Knowth - Schulting, R; Ramsey, C; Reimer, P; Eogan, G; Cleary, K; Cooney, G; Sheridan, A (Royal Irish Academy, 2017)
The 60 AMS 14C determinations on cremated and non-burnt human bone presented here have provided a robust chronological framework for the interpretation of the main use phase at Knowth. This large series was seen as necessary to overcome the problem presented by the late fourth-millennium BC calibration plateau. To a large extent this strategy has been successful, but as is usually the case with modelling, there is not necessarily a single, clear-cut answer to questions of chronology, and much still depends on archaeological interpretation. Although the use of individual tombs is more variable, largely because of smaller sample sizes, overall modelling of funerary activity at Knowth consistently places the main phase of use as lasting between 100 and 300 years, maximum, in the period 3200-2900 BC (in a statement that now appears prescient, George Eogan (1991, 112) more than two decades ago suggested a date range of 3200-3000 cal. BC for the main phase of passage tomb construction and use at Knowth).